Success is dependent on effort: Unraveling characteristics of successful deer and elk hunters - Mary M. Rowland; Ryan M. Nielson; Michael J. Wisdom; Darren A. Clark; Guy T. DiDonato; Jennifer M. Hafer; Bridgett J. Naylor; Bruce K. Johnson (Wildlife Society Bulletin, 2023)
Abstract The pursuit of ungulates as game animals, whether for recreation, cultural tradition, or meat, is a dominant activity on public and private lands in North America and much of the world. Strategic regulation of hunting is key for managing game population abundance, age and sex structure, and distribution, with harvest rates a function of both hunter success and participation. Hunter satisfaction is often linked to success and ultimately with hunter recruitment and retention, a growing concern for wildlife agencies. Yet knowledge is lacking about what hunter characteristics or behaviors are linked with success, and how these may differ among common hunt types. We used survey and spatial data from hunters (n = 416) during a 6‐year observational study in northeastern Oregon, USA to characterize hunter traits associated with success for 3 hunt types for antlered males: rifle deer (Odocoileus spp.), archery elk (Cervus canadensis), and rifle elk. We modeled the success for rifle deer and rifle elk hunters using logistic regression models in a Bayesian hierarchical approach. Annual success rates were highly variable, ranging from 4 to 76% for rifle deer and 20 to 56% for rifle elk hunters, and from 0 to 14% for archery elk. Age distributions of hunters were similar across hunt types (x ̅ = 47.2 years), and male hunters were ~8 times as common as females (n = 370 vs. n = 46, respectively). Success rates for men and women, however, were comparable within hunt types. Successful hunters spent more hours per day outside camp (x ̅ = 7.4 vs. 6.4 for unsuccessful hunters) and expended a slightly larger percentage of their hunting effort on foot (x ̅ = 87.8%) than did unsuccessful hunters (x ̅ = 84.6%). The best model predicting success of rifle deer hunters was based on hours per day spent outside camp during the hunting hours, with each additional hour increasing odds of success by 26%. For rifle elk hunters, the best model included time outside camp and a binary covariate for scouting. The odds of success increased by 418% for hunters who scouted versus those who did not, and by 18% with each additional hour per day spent hunting outside of camp. Summed model weights indicated that hours per day outside camp and scouting were most informative, and that use of an all‐terrain vehicle, age, and experience were unrelated to hunter success. Both models performed reasonably well (correct classification rates of 0.74 and 0.70 for rifle deer and rifle elk models, respectively). Our study augmented the relatively limited published information about behavioral factors associated with successful harvest of deer and elk, and we recommend additional research to better unravel the nexus of success and hunter characteristics and behavior to help sustain recreational hunting and big game populations.